دور بعض العوامل الفيزيائية للتربة والتسميد الفوسفاتي في إنتاجية الذرة الصفراء ونموها في سهل الغاب - ترت محمد; المحمود فاطمة; اليوسف نزار (Latakia University Journal -Biological Sciences Series, 2019)
أجريت التجربة في أصص تحت الظروف الطبيعية لمعرفة تأثير مستويات رطوبة مختلفة (60، 70، 100 %) من السعة الحقلية والقوام (طينية، لومية، رملية) وتحت مستويات من السماد الفوسفاتي (0/50/75/100 كغ P2O5 / هـ) في نمو الفسفور وامتصاصه من قبل نبات الذرة الصفراء. بينت النتائج أن التربة الرملية أعطت أعلى قيمة للوزن الجاف والفسفور الممتص في الجزء الخضري والجذور تحت تأثير المستوى الرطوبي 100 % والإضافة السمادية 100 كغ P2O5 / هـ. أما التربة اللومية ذات المستوى الرطوبي 100 % وتحت الإضافة السمادية الفوسفاتية 100 كغ P2O5 / هـ أعطت أعلى قيمة للوزن الجاف للجزء الخضري والجذور والفسفور الممتص، بينما أعطت التربة الطينية قيماً مرتفعة للوزن الجاف للجزء الخضري تحت تأثير المستوى الرطوبي 70 % مع 75 كغ P2O5 / هـ سماد فوسفاتي. عموماً فإن القوام اللومي أعطى أعلى وزن جاف وفسفور ممتص تحت تأثير رطوبة 100 % وإضافة سمادية 100 كغ P2O5 / هـ مقارنة بالقوام الطيني و القوام الرملي. A pot experiment was conducted under natural conditions to determine the effect of different moisture levels (60, 70, 100%) of the field capacity, texture (clay, loam, sand), and under different levels of phosphorus fertilizer (0, 50, 75, 100 kg P2O5 / ha) on growth and P-uptake by Zea Mays. The results showed that the sandy soils gave the highest dry weight and P-uptake value to the green part and roots under moisture level 100% and under the addition of phosphorus fertilizer 100 kg P2O5 /ha. The loam soil of 100 % moisture level and under the phosphorus fertilizer addition 100 kg P2O5 /ha gave the highest value to the dry weight of the green part, roots and P-uptake. Whereas clay soil gave the highest value to dry weight of the green part under the effect of 70% moisture levels with 75 kg P2O5 /ha phosphorus fertilizer. Generally, the loam texture gave a higher dry weight and P-uptake under 100 % moisture and fertilizer addition 100 kg P2O5 / ha compared with the clay and sand texture.